Fat crystallization of blends of palm oil and anhydrous milk fat: A comparison between static and dynamic-crystallization. (November 2020) - Nguyen, Viet; Rimaux, Tom; Truong, Vinh; Dewettinck, Koen; Van Bockstaele, Filip
Graphical abstract: Highlights: Dynamic–crystallization can prevent the formation of β crystals in fat blends. Post–crystallization events for static and dynamic–crystallized blends are similar. Post–hardening event is stronger for dynamic–crystallized blends. Granular crystals are mainly formed through recrystallizing high melting TAGs. Abstract: The application of dynamic-crystallization (a combination of shear with rapid cooling) often plays an important role in the production of industrial fat-based products such as shortenings/margarines but has been rarely reported. In this study, three blends of palm oil (PO) with anhydrous milk fat (AMF) (0, 25 and 50% AMF, w/w) were rapidly crystallized under static (using freezer) and dynamic conditions (using a benchtop scraped surface heat exchanger). Various techniques including differential scanning calorimetry (DSC), X-ray diffraction (XRD), polarized light microscopy (PLM), rheology and texture analysis were applied to investigate physicochemical properties of fat blends as well as their crystal morphology upon the long-term storage (4 weeks) at 5 °C and 15 °C. The results revealed that high cooling rate of dynamic-crystallization not only affected melting behavior of fat blends but also prevented the polymorphic transformation from β' to β crystals. Besides, the application of shear during fat crystallization helped to improve significantly the gel strength of produced shortenings. Although post-crystallization of low melting triacylglycerols (TAGs) occurred for all produced shortenings during storage at 5 °C which was accompanying with a firmness increase, it was more considerable for samples owning higher AMF content. Moreover, this phenomenon promoted the sintering as well as Ostwald ripening between fat crystals of dynamic-crystallized fat blends resulting in the formation of unwanted large aggregates (or granular crystals) with the size ranging from 100 to 500 μm.